2021
DOI: 10.3390/jpm11030225
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Left Ventricular Function Persisting during Post-Acute COVID-19 in Subjects without Previously Diagnosed Cardiovascular Pathology

Abstract: (1) Background: Coronavirus infection (Covid-19) has emerged as a severe medical condition, associated with high pulmonary morbidity and often with cardiovascular (CV) complications. This study aims to evidence the persistence of left ventricular (LV) systolic function (LV-SF) alterations and diastolic dysfunction (DD) in COVID-19 patients without history of cardiovascular (CV) diseases by transthoracic echocardiography (TTE). (2) Methods: 125 patients, aged under 55 years, hospitalized during the first outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 30 publications
3
35
3
1
Order By: Relevance
“…50,53,54,60 LV diastolic dysfunction was observed in 16%, and systolic dysfunction in 10% of COVID-19 patients. 46,61…”
Section: Left Ventricular (Lv) Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…50,53,54,60 LV diastolic dysfunction was observed in 16%, and systolic dysfunction in 10% of COVID-19 patients. 46,61…”
Section: Left Ventricular (Lv) Involvementmentioning
confidence: 99%
“…But DD seems to be more common than systolic dysfunction in patients with COVID-19(16% vs 10%). 46,61…”
Section: Diastolic Dysfunction (Dd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted with patients hospitalized with a diagnosis of COVID-19, although there was no difference in LVEF and LV diastolic dysfunction (E/a') between those that died and those that survived, it was reported that MAPSE was lower in the former, and it was an independent predictor of mortality 6 . In a study including patients who had been hospitalized with a diagnosis of mild to moderate COVID-19 pneumonia and discharged, who had no known history of cardiovascular disease, echocardiography was performed in the postacute COVID phase (<12 weeks), and LV dysfunction was detected in 8.8% of patients and diastolic dysfunction in 16.8% 19 . In another study, patients hospitalized with a diagnosis of COVID- 19 and discharged underwent echocardiography one month after the first detection of infection, and the RV and LV functions did not vary between the control and patient groups 20 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the frequent observations was the LV's diastolic dysfunction, which was found in up to 16% of COVID-19 patients [64]. A reduced LV ejection fraction (LVEF) was less common than diastolic dysfunction, with a reported prevalence of 10% [65]. Wall motion abnormalities were reported in 14 to 26% of the COVID-19 patients who underwent echocardiography.…”
Section: Echocardiographymentioning
confidence: 99%